KEPUASAN KONSUMEN TERHADAP PASTA GIGI DAUN SIRIH (Piper betle L.) DI KOTA SURAKARTA - Aprilia Yuanita Anwaristi (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2021)
The widespread use of betel leaf herbal toothpaste was because that toothpaste has commercially available and recently the interest in products based on natural ingredients has increased. This study aimed to determine the level of consumer satisfaction with the attributes of betel leaf toothpaste in Surakarta. Data analysis using the CSI (Customer Satisfaction Index) method. The research was conducted from August to November 2020 in various supermarkets in Surakarta with 100 consumers as respondents. The results showed that consumer satisfaction with betel leaf toothpaste in the supermarket in Surakarta was in the satisfied category (70.56%). The order of consumer satisfaction with the attributes of betel leaf toothpaste is the attribute of toothpaste color, taste, price, and packaging. Consumers are satisfied because their expectations in shopping for betel leaf toothpaste at supermarkets in Surakarta have been fulfilled.